Penerapan Nilai-Nilai Sosial dan Keagamaan Melalui Kegiatan Ekstrakurikuler Keagamaan dalam Pendidikan Anak Usia Dini - Maya Aprianti; Sukrin Sukrin; Wahyu Mulyadi (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2026)
This study analyzes the internalization of social and religious values through religious extracurricular activities in early childhood education at RA Al-Nizum Hidayah. A qualitative case study approach was used to explore how value internalization is implemented and reflected in children’s behavior, with data collected through observations, interviews with the head of RA and teachers, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Internalization is understood as a gradual process in which values are introduced, practiced, and reinforced until reflected in daily behavior, while social and religious values include discipline, responsibility, cooperation, empathy, and adherence to basic Islamic practices. The findings show three mechanisms: habituation (daily prayers, Qur’anic memorization, and charity), modeling (teachers demonstrating respectful and disciplined behavior), and guided practice (assistance in congregational prayer and structured interaction). These mechanisms are associated with children initiating prayers independently, increased rule compliance, active group participation, and early empathy such as sharing and helping peers. The study suggests that integrating structured activities and teacher role modeling supports the gradual formation of socio-religious behavior, with its novelty lying in proposing a three-stage internalization model based on empirical observations.